Contact and role modeling predict bias against lesbian and gay individuals among early-career physicians: A longitudinal study. (October 2019) - Wittlin, Natalie M.; Dovidio, John F.; Burke, Sara E.; Przedworski, Julia M.; Herrin, Jeph; Dyrbye, Liselotte; Onyeador, Ivuoma N.; Phelan, Sean M.; van Ryn, Michelle
Abstract: Rationale: Physician bias against sexual minorities can hinder the delivery of high-quality health care and thus contribute to the disproportionate prevalence of negative health outcomes within this population. Medical students' interpersonal experiences within the context of medical school may contribute to this bias. Objective: The goal of the current research was to examine the relationship between these interpersonal experiences, reported by heterosexual, cisgender medical students, and explicit and implicit bias against lesbians and gay individuals, reported two years later during second year of medical residency. Method: Data were collected by surveying students ( n = 2940) from a stratified sample of U.S. medical schools in fall 2010 (first semester of medical school), spring 2014 (final semester of medical school), and spring 2016 (second year of medical residency). Results: Amount and favorability of contact with LGBT individuals, reported during the final semester of medical school, predicted lower levels of explicit bias against lesbian and gay individuals during second year of medical residency. Additionally, exposure to negative role modeling, also reported during the final semester of medical school, predicted higher levels of explicit bias against lesbian and gay individuals during second year of medical residency. Amount of contact with LGBT individuals – and in particular, with LGBT medical students – predicted lower levels of implicit bias against lesbian and gay individuals during second year of medical residency. Neither favorability of contact with LGBT individuals nor exposure to negative role modeling predicted implicit bias against lesbian and gay individuals during second year of medical residency. Conclusion: These results suggest that interpersonal experiences during medical school can systematically shape heterosexual, cisgender physicians' subsequent explicit and implicit bias against lesbian and gay individuals. Highlights: Medical schools' informal curricula can have enduring effects on anti-LG bias. More LGBT contact predicted less physician explicit anti-LG bias. More favorable LGBT contact predicted less physician explicit anti-LG bias. Greater exposure to anti-LGBT bias predicted more physician explicit anti-LG bias. More contact with LGBT peers predicted less physician implicit anti-LG bias.